Understanding the relationship between resource scarcity and object attachment. (June 2021) - Goldsmith, Kelly; Roux, Caroline; Cannon, Christopher
Abstract : People generally respond to resource scarcity through one of two pathways: scarcity-reduction or control-restoration. We draw from recent work on the solidity (versus liquidity) of consumption opportunities to offer a new lens through which to view how the two pathways that follow from resource scarcity relate to object attachment. In this review, we discuss when each pathway predicts stronger (versus weaker) object attachment. We also offer several open questions for when resource scarcity might prompt consumers to forgo the security afforded by stronger attachments for the flexibility afforded by weaker attachments.